KESIAPAN DAN PERSEPSI GURU TERHADAP IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA DI SMA SWASTA X DI YOGYAKARTA - Siti, Kristina; Gopito, Florensia Eka; Freitas, Celia Maria Antonia Da Costa; Prijowuntato, Sebastianus Widanarto (STKIP Pesisir Selatan, 2025)
This study aims to analyze teacher readiness and perceptions in implementing differentiated learning within the Independent Curriculum (Curriculum Merdeka) at a private high school in Yogyakarta. The research method used was descriptive quantitative, with a Likert-scale questionnaire administered to 45 teachers. The results showed that most teachers understood the concept of differentiated learning and demonstrated the ability to identify student learning needs. School support for the implementation of this learning was considered quite good, although some teachers felt they had not received full support. Furthermore, teachers' confidence in designing differentiated learning varied; some teachers felt ready, while others remained uncertain. Key obstacles include time constraints, high class sizes, and administrative burdens that limit teachers' room for innovation. These findings confirm that the success of differentiated learning depends not only on teachers' conceptual understanding but also on institutional support and school policies. Therefore, ongoing training, reduced administrative burdens, and policies that better support learning innovation are needed.